Chemo-radiotherapy with 177Lu-PLGA(RGF)-CXCR4L for the targeted treatment of colorectal cancer - Cruz-Nova, Pedro; Gibbens-Bandala, Brenda; Ancira-Cortez, Alejandra; Ramírez-Nava, Gerardo; Santos-Cuevas, Clara; Luna-Gutiérrez, Myrna; Ocampo-García, Blanca (Frontiers in Medicine, 2023)
Introduction More than 1.9 million new cases of colorectal cancer and 935,000 deaths were estimated to have occurred worldwide in 2020. Therapies for metastatic colorectal cancer include cytotoxic chemotherapy and targeted therapies in multiple lines of treatment. Nevertheless, the optimal use of these agents has not yet been resolved. Regorafenib (RGF) is an Food and Drug Administration (FDA)-authorized multikinase inhibitor indicated for patients with metastatic colorectal cancer, non-responding to priority lines of chemotherapy and immunotherapy. Nanoparticles have been used in specific applications, such as site-specific drug delivery systems, cancer therapy, and clinical bioanalytical diagnostics. C-X-C Chemokine receptor type 4 (CXCR4) is the most widely-expressed chemokine receptor in more than 23 human cancer types, including colorectal cancer. This research aimed to synthesize and preclinically evaluate a targeted nanosystem for colorectal cancer chemo-radiotherapy using RGF encapsulated in Poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles coated with a CXCR4 ligand (CXCR4L) and 177Lu as a therapeutic β-emitter. Methods Empty PLGA and PLGA(RGF) nanoparticles were prepared using the microfluidic method, followed by the DOTA and CXCR4L functionalization and nanoparticle radiolabeling with 177Lu. The final nanosystem gave a particle size of 280 nm with a polydispersity index of 0.347. In vitro and in vivo toxicity effects were assessed using the HCT116 colorectal cancer cell line. Results 177Lu-PLGA(RGF)-CXCR4L nanoparticles decreased cell viability and proliferation by inhibiting Erk and Akt phosphorylation and promoting apoptosis. Moreover, in vivo administration of 177Lu-PLGA(RGF)-CXCR4L significantly reduced tumor growth in an HCT116 colorectal cancer xenograft model. The biokinetic profile showed hepatic and renal elimination. Discussion Data obtained in this research justify additional preclinical safety trials and the clinical evaluation of 177Lu-PLGA(RGF)-CXCR4L as a potential combined treatment of colorectal cancer.